2018
DOI: 10.1038/s41388-017-0057-3
|View full text |Cite
|
Sign up to set email alerts
|

miR-139-5p inhibits aerobic glycolysis, cell proliferation, migration, and invasion in hepatocellular carcinoma via a reciprocal regulatory interaction with ETS1

Abstract: Cancer cells have metabolic features that allow them to preferentially metabolize glucose through aerobic glycolysis, providing them with a progression advantage. However, microRNA (miRNA) regulation of aerobic glycolysis in cancer cells has not been extensively investigated. We addressed this in the present study by examining the regulation of miR-139-5p on aerobic glycolysis of hepatocellular carcinoma (HCC) using clinical specimens, HCC cells, and a mouse xenograft model. We found that overexpressing miR-13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 45 publications
9
62
0
Order By: Relevance
“…Previous studies have shown that miR‐139‐5p decreases cancer cell growth in many different types of cancers . Similarly, our data show decreased proliferation and migration in PC3 and Du145 PCa cell lines overexpressing miR‐139 compared with control cells (Figures and ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous studies have shown that miR‐139‐5p decreases cancer cell growth in many different types of cancers . Similarly, our data show decreased proliferation and migration in PC3 and Du145 PCa cell lines overexpressing miR‐139 compared with control cells (Figures and ).…”
Section: Discussionsupporting
confidence: 85%
“…AXL also activates the PI3K/AKT cascade . AKT activation leads to cyclin D1 upregulation through inhibition of GSK3β . Cyclin D1 then stimulates cell cycle entry and proliferation .…”
Section: Discussionmentioning
confidence: 99%
“…Among all PFKFBs, PFKFB3 exerts a central role in controlling glycolysis flux and has aroused a great deal of attention in recent years . In addition to activation of mTORC1, inactivated mutation of Pten or the aberrant activation of Ras and PI3K have been shown that take part in the regulation of glycolysis and tumorigenesis through modification of PFKFB3 expression . However, the detailed transcriptional regulation mechanisms of PFKFB3 expression are far from fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al demonstrated that the transcription factor PU.1 upregulates PFKFB3 which is responsible for the chemoresistance in chronic myeloid leukemia . The transcription factor ETS1 has been shown to promoted glycolysis through directly binding to the promoter of PFKFB3 and enhanced its transcription in hepatocellular carcinoma . In addition, transcription factors KLF2 and STAT5 also participate in the tumorigenesis through regulating PFKFB3 expression in different cancer cell content.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, besides CpG islands, there were also some DMRs located within noncoding regions, which harbor microRNA, lncRNA, cirRNA, and so forth, implicating that DNA hypermethylation may interact with noncoding RNA to regulate gene expression. In HCC, it had been reported that DNA hypermethylation can mediate epigenetic silencing of some tumor‐suppressive miRNAs, such as miR‐9, miR‐124, miR‐129, miR‐139, miR‐200b, and miR‐203 …”
Section: Discussionmentioning
confidence: 99%